Solution to the Problem of Costs of Medicines and Medical Devices (Alkes) Judging from Law no. 17 of 2023 concerning Health - Burnama, Eko C.; Daulay, Najib Albana; Nasution, Mira Husna; Radhiyah, Desy; Sitinjak, Yusuf (PT. Sinergi Legal Publisher, 2024)
It is hoped that the Omnibus Law Law No. 17 of 2023 concerning Health will provide solutions to various problems in the health sector. Such as health services which are still dominated by curative approaches, availability and distribution of Health Resources (HR), readiness to face health crises, aspects of pharmaceutical independence and Medical Devices. One of the most important issues in the transformation of the health resilience system is the high cost of health services in Indonesia, one of the causes of which is the high price of pharmaceutical preparations and medical devices in Indonesia. Through this law, the government is implementing solutions to prioritize raw materials at the Domestic Component Level, providing fiscal and non-fiscal incentives, marketing certainty and incentives in research development. It's just that the ethical approach is not listed. Derivative regulations that discuss follow-up solutions to the high prices of pharmaceutical preparations and health equipment are still urgently needed.